2023
DOI: 10.3390/ani13111772
|View full text |Cite
|
Sign up to set email alerts
|

Struggling Thermal Stress Impacts on Growth Performance and Health Status of Newly Weaned Rabbits Using Nanoemulsion of Origanum majorana Considering the Economic Efficiency of Supplementation

Abstract: With the recent trend of global warming, HS-instigated diminishing could extremely jeopardize animal health, productivity, and farm profit. Marjoram essential oil (MEOE) is a worthy source of wide range phytogenic compounds that may improve heat tolerance, redox and inflammatory homeostasis, and immunity of newly weaned rabbits, specifically if included in the diets in a nano form. One hundred newly weaned rabbits were randomly distributed into four homogeneous groups. The first group (control group) included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The above results indicate that the better growth performance of the NCEO-supplemented rabbits was achieved by enhancing the defeasibility of nutrients, which provide available energy for growth and heat dissipation from the body. In this study, the NCEO300 and NCEO600 groups had a higher FBW, ADG, SGR, and PI and a lower FCR than the control and other treated groups, which is in general agreement with the findings of former studies [ 36 , 40 ]. They reported that the dietary supplementation of rabbit diets with nano-emulsified essential oils enhanced their growth performance and feed utilization.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The above results indicate that the better growth performance of the NCEO-supplemented rabbits was achieved by enhancing the defeasibility of nutrients, which provide available energy for growth and heat dissipation from the body. In this study, the NCEO300 and NCEO600 groups had a higher FBW, ADG, SGR, and PI and a lower FCR than the control and other treated groups, which is in general agreement with the findings of former studies [ 36 , 40 ]. They reported that the dietary supplementation of rabbit diets with nano-emulsified essential oils enhanced their growth performance and feed utilization.…”
Section: Discussionsupporting
confidence: 93%
“…Rabbits have few numbers of sweat glands, mainly under their feet and on their lips. These sweat glands are not effective at regulating exceeded body temperature, particularly in hot conditions, which makes them more sensitive to HS, which has adverse effects on their welfare, adaptation, feed efficiency, growth performance, redox status, inflammatory response, and health status [ 7 , 35 , 36 ], and also disrupts the fertility traits in rabbit does [ 7 ] and bucks [ 37 ]. The temperature–humidity index (THI) can be useful for assessing the risk of HS on rabbits induced by hot environments [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the experiment (12 weeks), a total of 12 rabbits (n = 3 in each treatment) were randomly chosen and fasted for 12 hours before slaughter according to El-Raghi et al (2023). Then, the rabbits were individually weighed and the pre-slaughter weight was recorded.…”
Section: Carcass Characteristics and Internal Organsmentioning
confidence: 99%
“…Oregano essential oil can inhibit methane production in rumen of beef cattle [ 14 ]. Adding oregano oil to feed can improve the performance of rabbits, chickens and dairy cows [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%